Minor Volatile Compounds in Traditional Homemade Fruit Brandies from Transylvania-Romania, as Determined by GC-MS Analysis - Teodora Emilia COLDEA; Carmen SOCACIU; Zaharie MOLDOVAN; Elena MUDURA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2014)
In order to investigate the minor volatile compounds of traditional homemade fruit brandies from Romania (Transylvania region), as a result of their assortment and provenience, a number of 26 samples (18 plum brandies samples from 3 different counties, 4 samples of apple brandy and 4 samples of pear brandy) were analyzed using liquid-liquid extraction and gas-chromatography coupled with mass-spectrometry (GC-MS) technique. The GC-MS chromatograms of the hexane extracts led to the identification of 34 compounds (9 terpenes, 14 fatty acids esters, 3 free fatty acids, 4 carboxylic acid esters, 1 hydrocarbon, 1 aldehyde and 1 acetal). The most abundant compounds were the fatty acid esters. Chemometric analysis (Principal Component Analysis-PCA) was applied to discriminate the differences between the volatiles’ fingerprint. Considering the plum brandy samples, significant differences have been observed according to their provenience region. Based on relative abundance of determined compounds important differences among samples from different counties can be seen.. Ethyl hexadecanoate was the main factor for this discrimination. When compared the three types of fruit brandies, significant differences were noticed for their content in ethyl esters of hexanoic, benzoic and hexadecanoic acids. For some plum brandies, according to their fingerprint, possible adulteration with apple brandy can be noted, based on their similar volatiles’ pattern. The pear brandy was strongly delimitated by the other two types of brandies. The PCA data showed a good discrimination according to the region of provenience of the plum brandies in parallel with the composition specificity of the three analyzed fruit brandies.